The place of practice in tertiary popular music studies: An epistemology. Issue 1 (1st March 2017) - Weston, Donna
This article explores the potential role of popular music studies when integrated into popular music practice programmes in higher education, and proposes that purely theoretical popular music studies could inform creative practice in the education of popular music practitioners. In bringing popular music studies and popular music practice together under the banner of popular music education, it is proposed that popular music practice educators should consider the study of popu- lar music from a sociocultural perspective as well as a practical one. The argument is informed by two field reports that map higher education in popular music in the United Kingdom and in Australia, respectively, supported by responses of students to the integration of popular music studies into an Australian popular music prac- tice programme. The findings show that students of popular music practice benefit- ted from the inclusion of popular music studies into their curriculum through the development of critical listening skills and songwriting ability, expansion of a range of vocational skills and a stronger sense of purpose within the music industry.